THE STABILITY OF TAX REVENUE IN LOCAL GOVERNMENT UNITS IN YEARS 2005-2014 - Adam Żabka; Beata Hoza (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
Implementation of tasks assigned to local governments requires assigning them to sources of funding to finance expenses associated with their performing. Revenues generated from assigned to local government sources, in accordance with the tax rules, should be efficient and stable. The aim of the study, which was summed up in this paper, was therefore to analyse the stability of the own revenues of local government units. The study was conducted using methods of statistical analysis of indicators of tax revenues per capita of municipalities, counties and voivodeships.